Single mixing and single sintering process for manufacturing gallium and zinc doped lithium lanthanum zirconium oxide
Patent Information
- Application Number
- CN202411206025.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2026-03-17
AI Technical Summary
Existing lithium lanthanum zirconium oxides are inadequate in terms of ionic conductivity, mechanical properties, and interfacial impedance, and are also expensive. Existing dopants cannot significantly improve battery efficiency.
A single-mixing and single-sintering process was adopted, in which zinc oxide and gallium were added to lithium lanthanum zirconium oxide, followed by uniform mixing, grinding, drying and two-stage gas injection sintering, to form gallium and zinc doped lithium lanthanum zirconium oxide Li7-aLa3Zr1.7-xGayZnzO12.
This study improved the ionic conductivity of lithium lanthanum zirconium oxide, enhanced its mechanical properties, reduced its interfacial impedance, suppressed side reactions, and lowered its production costs, thus broadening its application prospects in solid-state batteries.
Smart Images

Figure CN121672576A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a process for solid electrolytes, and more particularly to a single-mixing and single-sintering process for manufacturing gallium- and zinc-doped lithium lanthanum zirconium oxide. Background Technology
[0002] In battery manufacturing, lithium lanthanum zirconium oxide (LLZO) is a novel solid electrolyte with excellent ionic conductivity and stability, making it an ideal material for solid-state lithium batteries.
[0003] Traditionally, the method of manufacturing solid electrolytes for lithium batteries using compounds such as zirconium dioxide (ZrO2), lanthanum oxide (La2O3), and lithium carbonate (Li2CO3) involves mixing and grinding a slurry of the three initial compounds in a certain proportion in a ball mill, and then sintering it once with oxygen during the reaction to generate lithium lanthanum zirconium oxide.
[0004] However, existing lithium lanthanum zirconium oxides (LLZOs) still require improvement in terms of ionic conductivity, mechanical properties, interfacial impedance, and other aspects. Some researchers have modified LLZOs by adding gallium to improve overall battery performance. However, this doping method still fails to achieve optimal battery efficiency. Therefore, the inventors aim to propose a gallium- and zinc-doped LLZO. Zinc oxide offers several advantages for modifying LLZO, including improved ionic conductivity, enhanced mechanical properties, reduced interfacial impedance, suppression of side reactions, and cost reduction.
[0005] Therefore, the present invention aims to propose a novel single-mixing and single-sintering process for manufacturing gallium and zinc-doped lithium lanthanum zirconium oxide, in order to overcome the aforementioned deficiencies in the prior art. Summary of the Invention
[0006] The purpose of this invention is to solve the problems mentioned above in the prior art. This invention proposes a single-mixing and single-sintering process for manufacturing gallium- and zinc-doped lithium lanthanum zirconium oxide. The addition of zinc oxide in this invention has multiple advantages for modifying LLZO, including improved ionic conductivity, enhanced mechanical properties, reduced interfacial impedance, suppression of side reactions, and reduced costs. These advantages make LLZO-ZnO composite materials promising for applications in solid-state batteries. The advantages of ZnO doping in LLZO are mainly reflected in the following aspects: improved mechanical properties: enhancing the strength and toughness of the material; improved interfacial compatibility: reducing interfacial impedance and improving battery performance.
[0007] To achieve the above objectives, this invention proposes a single-mixing and single-sintering process for manufacturing gallium- and zinc-doped lithium lanthanum zirconium oxide, comprising: Step A: taking lithium carbonate powder; lanthanum oxide powder; zirconium dioxide powder; gallium oxide powder; and zinc oxide powder; and mixing the powders in an emulsifier to form a uniform mixed powder; Step B: grinding the mixed powder in a wet mill to obtain multiple mixed powders; wherein the wet mill also includes water as a medium; Step C: drying the multiple mixed powders in an oven to remove moisture, thereby obtaining multiple blocky mixtures, and then placing the multiple blocky mixtures into... Step D: The mixture of fine powders is ground in a grinding bowl to form multiple fine powders. Step E: The fine powders are placed in a sintering furnace for sintering. The sintering temperature is raised from room temperature to 800℃~900℃. During the process of raising the temperature to 800℃~900℃, rare oxygen gas is injected into the sintering furnace. The rare oxygen gas system refers to the gas in which the proportion of oxygen is less than 30%. Step E: When the temperature reaches 800℃~900℃, the original rare oxygen gas is replaced with pure oxygen and injected into the sintering furnace. The furnace is then held at 800℃~900℃ for a certain period of time to complete the sintering process and obtain the gallium and zinc doped lithium lanthanum zirconium oxide.
[0008] Furthermore, the chemical formula of this gallium- and zinc-doped lithium lanthanum zirconium oxide is:
[0009] Li 7-a La3Zr 1.7-x Ga y Zn z O 12 ;
[0010] 2x + 3y + 2z = a
[0011] a>0, x>0, y>0, z>0.
[0012] Furthermore, the lithium carbonate powder contains between 20% and 25% by weight; the lanthanum oxide powder contains between 40% and 45% by weight; the zirconium dioxide powder contains between 20% and 25% by weight; the gallium oxide powder contains between 3% and 5% by weight; and the zinc oxide powder contains between 3% and 5% by weight.
[0013] Furthermore, the size of the multiple mixed powders is less than 1 micrometer.
[0014] Furthermore, the weight ratio of the pure water to the mixed powder is 8:2.
[0015] Furthermore, in step C, the oven temperature is 80±5℃, and the drying process lasts for 3 to 4 hours.
[0016] Furthermore, in step D, the sintering temperature is increased from room temperature to 800℃~900℃ at a heating rate of 2℃ / min;
[0017] In step E, the temperature is maintained for 10 hours. Attached Figure Description
[0018] Figure 1 This is a flowchart of the present invention.
[0019] Figure 2 This is a flowchart of steps A and B of the present invention.
[0020] Figure 3 This is a flowchart of step C of the present invention.
[0021] Figure 4 This is a flowchart of steps D and E of the present invention.
[0022] in,
[0023] 200. Emulsifier; 210. Wet grinder; 220. Oven; 230. Grinding bowl; 240. Sintering furnace. Detailed Implementation
[0024] The features and advantages of the invention will be further understood from the following description, and please refer to the accompanying drawings while reading.
[0025] The present invention will now be described in detail with reference to the accompanying drawings, along with a preferred embodiment of the invention.
[0026] I. Process for manufacturing gallium- and zinc-doped lithium lanthanum zirconium oxide
[0027] Please refer to Figures 1 to 4 As shown, the present invention provides a single-mixing and single-sintering process for manufacturing gallium and zinc-doped lithium lanthanum zirconium oxide. This process involves mixing lithium carbonate (Li₂CO₃) powder, lanthanum oxide (La₂O₃) powder, zirconium dioxide (ZrO₂) powder, gallium oxide (Ga₂O₃) powder, and zinc oxide (ZnO) powder using a single-mixing and single-sintering process to obtain gallium and zinc-doped lithium lanthanum zirconium oxide (Ga&Zn dope-LLZO). The single-sintering process includes two stages of gas injection: a first stage injecting dilute oxygen gas and a second stage injecting pure oxygen gas.
[0028] The process includes the following steps:
[0029] Step A:
[0030] Take lithium carbonate powder,
[0031] Lanthanum oxide powder,
[0032] Zirconium dioxide powder,
[0033] Gallium oxide powder,
[0034] and zinc oxide powder,
[0035] The lithium carbonate powder, lanthanum oxide powder, zirconium dioxide powder, gallium oxide powder, and zinc oxide powder are placed into an emulsifier 200 and mixed to form a uniform mixed powder.
[0036] The lithium carbonate powder contains 20% to 25% by weight; the lanthanum oxide powder contains 40% to 45% by weight; the zirconium dioxide powder contains 20% to 25% by weight; the gallium oxide powder contains 3% to 5% by weight; and the zinc oxide powder contains 3% to 5% by weight.
[0037] Step B: The mixed powder is placed in a wet grinder 210 for grinding for 2 hours to obtain multiple mixed powders with a particle size of less than 1 micrometer (D50 < 1 μm, where D50 refers to the median of the particle size distribution). The wet grinder 210 also includes pure water as a medium. The weight ratio of the pure water to the multiple mixed powders is 8:2.
[0038] Step C: Place the multiple mixture powders into an oven 220 for drying to remove moisture. The temperature of the oven 220 is approximately 80±5℃, and the drying process lasts for 3 to 4 hours, resulting in multiple block mixtures. Then, place the multiple block mixtures into a grinding bowl 230 for grinding to form multiple fine powders.
[0039] Step D: The multiple fine powder mixtures are placed into a sintering furnace 240 for sintering. The sintering temperature is increased from room temperature to 800℃~900℃ at a rate of 2℃ / min. During the process of heating to 800℃~900℃, rare oxygen gas is injected into the sintering furnace 240.
[0040] The rare oxygen system refers to a gas in which the proportion of oxygen is less than 30%, such as air. Because of its low oxygen content, the oxygen in this rare oxygen gas does not react effectively with other molecules during this stage of combustion, thus yielding high-purity cubic-phase lithium lanthanum zirconium oxide doped with gallium and zinc.
[0041] Step E: When the temperature reaches 800℃~900℃, the previously injected dilute oxygen gas is replaced with pure oxygen and injected into the sintering furnace 240. The injection method involves injecting liquid oxygen into the sintering furnace 240 and vaporizing it to replace the original air inside the furnace. The temperature is then held at 800℃~900℃ for 10 hours to complete the sintering process and obtain the sintered product, namely the gallium and zinc-doped lithium lanthanum zirconium oxide of this invention. A preferred holding temperature is 800℃.
[0042] During the sintering process, gallium and zinc from the gallium oxide and zinc oxide will enter the original lithium lanthanum zirconium oxide, partially replacing the lithium and zirconium within it, thus forming the gallium- and zinc-doped lithium lanthanum zirconium oxide. Its chemical formula is:
[0043] Li 7-a La3Zr 1.7-x Ga y Zn z O 12 ;
[0044] 2x + 3y + 2z = a
[0045] a>0, x>0, y>0, z>0.
[0046] Step F: High-purity gallium- and zinc-doped lithium lanthanum zirconium oxide can be extracted by filtration.
[0047] II. Physical specimens of gallium- and zinc-doped lithium lanthanum zirconium oxide
[0048] The present invention also includes gallium- and zinc-doped lithium lanthanum zirconium oxide produced by the above steps.
[0049] The gallium- and zinc-doped lithium lanthanum zirconium oxide is prepared by mixing lithium carbonate powder, lanthanum oxide powder, zirconium dioxide powder, gallium oxide powder, and zinc oxide powder in an emulsifier 200 to form a homogeneous powder mixture. This mixture is then ground in a wet mill 210 to obtain multiple powder mixtures. These powder mixtures are then dried in an oven 220 to remove moisture, resulting in multiple block-shaped mixtures. These block-shaped mixtures are then ground in a grinding bowl 230 to form multiple fine powder mixtures. Finally, these fine powder mixtures are placed in a sintering furnace 240 for a two-stage gas-injection sintering process. In the first stage, the sintering temperature is raised from room temperature to 800℃–900℃, and rarefied oxygen gas is injected into the sintering furnace 240. In the second stage, the previously injected rarefied oxygen gas is replaced with pure oxygen, and the sintering process is completed at 800℃–900℃ to obtain the gallium- and zinc-doped lithium lanthanum zirconium oxide. During the sintering process, gallium and zinc from the gallium oxide and zinc oxide will enter the original lithium lanthanum zirconium oxide, partially replacing the lithium and zirconium therein. This forms the gallium and zinc-doped lithium lanthanum zirconium oxide of the present invention.
[0050] The chemical formula of the gallium- and zinc-doped lithium lanthanum zirconium oxide 100 is:
[0051] Li 7-a La3Zr 1.7-x Ga y Zn z O 12 ;
[0052] 2x + 3y + 2z = a
[0053] a>0, x>0, y>0, z>0.
[0054] The lithium carbonate powder contains 20% to 25% by weight; the lanthanum oxide powder contains 40% to 45% by weight; the zirconium dioxide powder contains 20% to 25% by weight; the gallium oxide powder contains 3% to 5% by weight; and the zinc oxide powder contains 3% to 5% by weight.
[0055] The grinding process is carried out in a wet grinder 210 for 2 hours, resulting in a powder size of less than 1 micrometer (D50 < 1 μm, where D50 refers to the median of the particle size distribution). The wet grinder 210 also includes pure water as a medium. The weight ratio of the pure water to the mixed powder is 8:2.
[0056] During the oven drying process, the temperature of the oven (220) is approximately 80±5℃, and the drying process lasts for 3 to 4 hours.
[0057] During the first stage of sintering, the temperature is increased at a rate of 2℃ / minute.
[0058] The rarefied oxygen system refers to a gas in which the proportion of oxygen is less than 30%, such as air. Because of its low oxygen content, the oxygen in this rarefied oxygen gas does not react effectively with other molecules during this stage of combustion, thus yielding high-purity cubic gallium and zinc-doped lithium lanthanum zirconium oxide.
[0059] The addition of zinc oxide in this invention has several advantages, including: improving ionic conductivity and reducing the Li content in LLZO. + Diffusion barriers are eliminated, thereby increasing ionic conductivity. This helps improve the performance of solid-state electrolytes in lithium batteries. The addition of zinc oxide introduces specific defects into the LLZO lattice. These defects can act as hopping points for lithium ions, promoting their migration and thus improving ionic conductivity. Band structure: The introduction of zinc oxide may alter the band structure of LLZO, lowering the energy barrier for lithium ion migration and thus improving ionic conductivity. Furthermore, the presence of zinc oxide can reduce impedance at grain boundaries, which also significantly contributes to the overall improvement in conductivity.
[0060] Furthermore, Zn 2+ Ionic radius and Zr 4+ Similar, with Zn 2+ Ion-substituted Zr 4+ Afterward, oxygen vacancies can be generated, which can serve as fast channels for lithium-ion conduction.
[0061] The addition of zinc oxide can improve sintering properties: as a sintering aid, zinc oxide can lower the sintering temperature of LLZO and promote grain growth, thereby improving the material's density and mechanical strength. Phase diagram analysis of zinc oxide and LLZO can reveal their compatibility and phase stability at different temperatures. Under certain conditions, zinc oxide may form a liquid phase, promoting the sintering of LLZO, making the material denser, reducing resistance at grain boundaries, and facilitating ion conduction.
[0062] In addition, the addition of zinc oxide helps stabilize the cubic phase structure of LLZO, which typically has high lithium-ion conductivity.
[0063] Compared to other commonly used dopants, such as rare earth metal oxides like gallium oxide and tantalum oxide, zinc oxide doping in LLZO offers several unique advantages: First, it provides higher chemical stability: Zinc oxide-doped LLZO typically exhibits better chemical stability when in contact with lithium metal. This is because zinc oxide forms fewer byproducts when reacting with lithium than Ga₂O₃ and Ta₂O₃, which helps reduce interfacial side reactions and thus extend battery life. Second, it improves interfacial compatibility: Zinc oxide better improves the interfacial compatibility between LLZO and lithium metal electrodes. Compared to Ga₂O₃ and Ta₂O₃, zinc oxide-doped LLZO more easily forms a stable interfacial layer after contacting lithium metal, which helps reduce interfacial impedance. Interfacial energy: The interfacial energy between zinc oxide and electrode materials (such as LiCoO₂) may be low, which is conducive to forming a stable interface and reducing interfacial impedance.
[0064] From a cost perspective, zinc oxide is cheaper and more readily available than gallium oxide and tantalum oxide. This gives zinc oxide an economic advantage in large-scale production and applications, especially when considering cost-effectiveness. On the other hand, zinc oxide is a relatively environmentally friendly material and produces fewer byproducts during processing, which helps reduce the environmental impact of production. In contrast, certain dopants (such as tantalum oxide) may impose a higher environmental burden during production.
[0065] Zinc oxide, as a second-phase particle, can strengthen the LLZO matrix, improving the material's strength and toughness. Zinc oxide particles can also inhibit crack propagation, enhancing the material's fracture toughness.
[0066] Charge compensation: The introduction of zinc oxide can provide additional positive charge to compensate for the charge imbalance caused by lithium ion desorption and stabilize the structure of the material.
[0067] In summary, the addition of zinc oxide to modify LLZO offers numerous advantages, including increased ionic conductivity, improved mechanical properties, reduced interfacial impedance, suppression of side reactions, and reduced costs. These advantages make LLZO-ZnO composites promising for applications in solid-state batteries. The advantages of zinc oxide doping in LLZO are mainly reflected in the following aspects: improved mechanical properties: enhancing the strength and toughness of the material; improved interfacial compatibility: reducing interfacial impedance and improving battery performance.
[0068] The advantage of this invention lies in the addition of zinc oxide and gallium oxide to the lithium lanthanum zirconium oxide. Zinc oxide offers numerous advantages for modifying LLZO, including increased ionic conductivity, improved mechanical properties, reduced interfacial impedance, suppression of side reactions, and lower costs. These advantages make LLZO-ZnO composite materials promising for applications in solid-state batteries.
[0069] In summary, the human-centered and considerate design of this invention is highly suitable for practical needs. Its specific improvements over existing technologies demonstrate a significant breakthrough and substantial advancements compared to existing technologies, resulting in genuinely enhanced efficiency, which is not easily achieved. The foregoing detailed description pertains to a specific feasible embodiment of this invention; however, this embodiment is not intended to limit the scope of the invention. All equivalent implementations or modifications that do not depart from the technical features of this invention should be included within the scope of protection of this invention.
Claims
1. A single mixing and single sintering process for the manufacture of gallium and zinc doped lithium lanthanum zirconium oxide, characterized in that, Comprising: Step A: Take lithium carbonate powder; Lanthanum oxide powder; Zirconium dioxide powder; Gallium oxide powder; And zinc oxide powder; Put the above-mentioned powders into an emulsifier for mixing to become a uniform mixed powder; Step B: Put the mixed powder into a wet grinder for grinding to obtain a plurality of mixed powder; wherein the wet grinder also includes pure water as a medium; Step C: Put the plurality of mixed powder into an oven for drying to remove moisture to obtain a plurality of block-shaped mixture, and then put the plurality of block-shaped mixture into a grinding bowl for grinding treatment to form a plurality of mixed powder; Step D: Put the plurality of mixed powder into a sintering furnace for sintering treatment, and the sintering temperature is increased from room temperature to 800℃-900℃, and in the process of increasing the temperature to 800℃-900℃, inject a dilute oxygen gas into the sintering furnace; wherein the dilute oxygen gas refers to the proportion of oxygen in the entire gas is less than 30%; Step E: Until the temperature is increased to 800℃-900℃, replace the dilute oxygen gas originally injected into the sintering furnace with pure oxygen injection, and hold the temperature at 800℃-900℃ for a certain period of time to complete the sintering process to obtain the gallium and zinc doped lithium lanthanum zirconium oxide.
2. A single mix and single sinter process for the manufacture of gallium and zinc doped lithium lanthanum zirconium oxide as claimed in claim 1 wherein, The chemical formula of the gallium and zinc doped lithium lanthanum zirconium oxide is: Li 7-a La3Zr 1.7-x Ga y Zn z O 12 ; 2x+3y+2z=a, a>0, x>0, y>0, z>0.
3. A single mix and single sinter process for the fabrication of gallium and zinc doped lithium lanthanum zirconium oxide as claimed in claim 1 wherein, The weight percentage of the lithium carbonate powder is between 20%-25%; the weight percentage of the lanthanum oxide powder is between 40%-45%; the weight percentage of the zirconium dioxide powder is between 20%-25%; the weight percentage of the gallium oxide powder is between 3%-5%; and the weight percentage of the zinc oxide powder is between 3%-5%.
4. A single mix and single sinter process for the fabrication of gallium and zinc doped lithium lanthanum zirconium oxide as claimed in claim 1 wherein, The size of the plurality of mixed powder is less than 1 micron.
5. The single mix and single sinter process for the fabrication of gallium and zinc doped lithium lanthanum zirconium oxide as claimed in claim 1 wherein, The weight ratio of the pure water to the mixed powder is 8:
2.
6. A single mix and single sinter process for the fabrication of gallium and zinc doped lithium lanthanum zirconium oxide as claimed in claim 1 wherein, In step C, the temperature of the oven is 80±5℃, and the drying time is 3-4 hours.
7. A single mix and single sinter process for the fabrication of gallium and zinc doped lithium lanthanum zirconium oxide as claimed in claim 1 wherein, In step D, the sintering temperature is increased from room temperature to 800℃-900℃ at a temperature increasing rate of 2℃ / min; In step E, the holding temperature time is 10 hours.